Perancangan Sistem Pendukung Keputusan dalam Penentuan Program Studi Berbasis Online - Nurkhalik Wahdanial Asbara; Vera Alviani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The choice of course of study can be an important decision in a person's life and can have a huge impact on their career and future. Some of the problems that are often faced are lack of information, parental pressure, trends or social pressure, lack of experience, cost of lack of understanding of oneself. Faced with this problem, students may seek help from a counselor or career advisor, do their own research about the course of study, take personality tests, or seek practical experience in a different field. One solution is The study program determination system is usually carried out by prospective students or students who have completed upper secondary education and want to continue their education to the tertiary level. The method used is the fuzzy mamdani method. The Fuzzy Mamdani method uses linguistic rules to transform uncertain or ambiguous inputs or data into more understandable outputs or decisions. This method makes use of the fuzzy set concept, which can handle numerical values with more flexible and linguistically understandable degrees of membership. The test results of the application are satisfactory accuracy and objectivity values, with parameters (75,60,75). The availability of information is quite satisfactory with parameters (60,60,75), ease of use is quite satisfactory with parameters (60,75,90). Data security is unsatisfactory with parameters (50,75,125,150), feedback and evaluation are unsatisfactory with parameters (50,75,125,150). This research produces applications that can display, detailed information on study programs, provide user status tracking features, and process data on registrants and prospective students making it easier for campus managers to manage and process the data.